Observation and control of a ball on a tilting - Contreras Martinez, Dimel Arturo (2017)
The author of this thesis, "Dimel Arturo Contreras Martinez", thanks the FONDECYTCONCYTEC grant through the 2015-034 FONDECYT agreement, under which the present thesis "Observation and control of a ball on a tilting plate" was developed.